PENERAPAN PRINSIP AKUNTABILITAS DAN TRANSPARANSI PADA PENGELOLAAN BMT DI KOTA SURAKARTA (Studi pada BMT Al-Madinah) - Usnan Usnan (Jurnal Riset Keuangan dan Akuntansi, 2019)
This research was conducted with the aim to find out how the application of the principles of accountability and transparency in the management of the Baitul Maal wat Tamwil (BMT) in Surakarta City with a study at KSUS BMT Al-Madinah Surakarta, which was conducted in 2018. This research is qualitative research, where data obtained through interview techniques and documentation then analyzed descriptively.The results showed that BMT Al-Madinah Surakarta had applied the principle of accountability consisting of; (1) legal accountability through compliance with the fulfillment of institutional legal aspects and fulfillment of DPS requirements and the implementation of the role of DPS at BMT Al-Madinah, (2) process accountability with the existing jobdescription and reward and punishment for all employees and the implementation of the system information in implementing financial / accounting functions; (3) program accountability through the implementation of programs that are always strived to achieve targets and involve the role of BMT members in determining program plans and targets to be achieved. While the principle of transparency is applied by BMT Al-Medina through the mechanism of RAT and the delivery of various information related to financial information, management and activities carried out through mobile media (whatsapp). Keywords: Accountability, Transparency.